Contribution of edible flowers to the Mediterranean diet: Phytonutrients, bioactivity evaluation and applications. Issue 4 (21st March 2022) - Amrouche, Thanina Amel; Yang, Xuan; Capanoglu, Esra; Huang, Weisu; Chen, Qi; Wu, Lipeng; Zhu, Yuhang; Liu, Yuqi; Wang, Yixuan; Lu, Baiyi
Abstract: The Mediterranean diet is acknowledged to be the healthiest dietary pattern around the world, mainly based on plant foods from the rich Mediterranean flora. It is also known to increase longevity and have positive effects on chronic diseases. This review aimed to investigate the knowledge about the use and consumption of edible flowers as part of the Mediterranean cuisine, based on ethnobotanical and ethnopharmacological studies especially from the last 10 years, and highlight their uses as a nutritious and functional food. In this review, a total of 32 edible flower species used in the Mediterranean diet were listed with their phytochemical composition, edible applications, bioactive properties, and dose, highlighting their nutritional contribution to the Mediterranean diet as well as their health effects. Edible flowers are consumed and widely contribute to the health‐promoting properties of the Mediterranean diet through being good sources of macro and micronutrients that enhance the nutritive value of Mediterranean dishes and foods, as well as providing more phytonutrients. Based on this, Mediterranean dishes have the remarkable characteristics of being conducive to mitochondrial health and anti‐metabolic diseases. The functional components in edible flowers are clarified here, which might be considered as a new factor for rational diet, natural product development, and medical improvement. Abstract : This review aimed to investigate the knowledge about the use and consumption of edible flowers as part of the Mediterranean cuisine, based on ethnobotanical and ethnopharmacological studies especially from the last 10 years, and highlight their uses as a nutritious and functional food. In this review, a total of 32 edible flower species used in the Mediterranean diet were listed with their phytochemical composition, edible applications, bioactive properties, and dose, highlighting their nutritional contribution to the Mediterranean diet as well as their health effects.